Methodological challenges in researching activism in action: civil society engagement towards health for all. Issue 4 (7th August 2020) - Bodini, Chiara; Baum, Fran; Labonté, Ronald; Legge, David; Sanders, David; Sengupta, Amit
ABSTRACT: Civil society engagement around health care and population health improvement is an important driver towards Health for All. Research can improve the effectiveness of health activism by examining the resources, structures and strategies of civil society engagement. However, research to support such engagement faces epistemological and methodological challenges which call for specific research strategies. A four year multi-country study was undertaken by the People's Health Movement, a global network working for health for all. The research took place in six countries (Brazil, Colombia, DR Congo, India, Italy, South Africa) and globally, and was directed to understanding five domains of civil society engagement: movement building; campaigning and advocacy; capacity building; knowledge generation, access and use; and engaging with governance. The research plan and methods of data collection and analysis were tailored to address the objective of improving activist practice, while negotiating research challenges identified during the design phase. Results include insights into the practice of civil society engagement in relation to the five domains of activist practice, as well as experience gained in managing six methodological challenges which we describe as: making meaning, aligning research and action, managing power relations, valuing experiential knowledges, chaos and contingency, challenging preconceptions. Researching activism can produce useful insights into practice as well as support continuous improvement in the effectiveness of such activism. However, there are significant methodological challenges that can be addressed through appropriate strategies. More research, building on the approach described in this paper, can contribute to more effective civil society activism for health.